Recruitment during Covid and Trends for 2021 - Fu, Na; Nguyen, Tam; Prost, Barry (My University, 2020)
This report was based on a survey conducted by a research team based in Trinity College Dublin in conjunction with Yala, funded by Enterprise Ireland.The survey aims to explore the recruitment practices and key challenges organisations are facing, especially in the current challenging climate as a consequence of COVID-19 pandemic. The report of survey findings seeks to provide insights into current recruitment methods and key recruitment challenges within Ireland’s organisations. It also includes information on the organisations’ experience with recruitment agencies and their expectations about recruitment services. Based on an extensive literature review, a series of recruitment practices was identified to capture the participants’ experience and perspectives of recruitment within their current organisations. A survey was designed including questions from published articles to ensure the reliability and validity of the results. After being reviewed by staff from Yala, the online survey was distributed to 498 HR professionals and received 102responses. A detailed analysis of the data was then carried out to identify key recruitment practices, recruitment difficulties and the participants’ perspectives of using recruitment services.
Keywords: Recruitment, covid-19, challenges, trends, human resource management, business management; Digital Engagement; Digital Humanities; Inclusive Society